Pediatric hurdle-related acute injuries in track and field presenting to US emergency departments: descriptive epidemiology study - Radel, L. C.; Jones, J. C.; Garcia, K.; Soma, D. B.; Miller, S. M.; Sugimoto, D. (The Physician and Sportsmedicine, 2023)
Background Hurdling is a track event that is unique due to a combination of running and jumping over an apparatus. Since hurdling requires a special skillset with sprinting and jumping, athletes are at risk for various musculoskeletal injuries. However, there has been a paucity of studies describing the epidemiology of pediatric hurdle injuries.